Researching trends on stroke: bibliometric analysis of the highly cited papers - Fan, Li; Shi, Fuyan; Wang, Suzhen (Frontiers in Stroke, 2024)
This study assessed the progression of stroke using bibliometric methods. By March 31, 2024, highly cited papers on stroke were collected from the Web of Science Core Collection. Collaboration and keyword conjunction analyses, along with their visual representations, were conducted using VOSviewer.CiteSpace was employed to identify keywords and reference sources. A comprehensive review of 2,509 highly cited studies on stroke was conducted. Notably, the United States, China, and the United Kingdom have emerged as leading contributors to this research domain, with the New England Journal of Medicine having the highest number of publications. YUSUF S had the highest H-index among all authors. The key terms frequently encountered were'stroke,' 'atrial fibrillation,'and'cardiovascular disease.' This study performed a detailed bibliometric review of stroke research over the past decade, shedding light on the participation of various countries, organizations, authors, journals, and articles in the field. These insights offer a broad snapshot of the global stroke research trends.